Respiratory pandemics, urban planning and design: A multidisciplinary rapid review of the literature. (August 2022) - Harris, Patrick; Harris-Roxas, Ben; Prior, Jason; Morrison, Nicky; McIntyre, Erica; Frawley, Jane; Adams, Jon; Bevan, Whitney; Haigh, Fiona; Freeman, Evan; Hua, Myna; Pry, Jennie; et al.
Abstract: COVID-19 is the most recent respiratory pandemic to necessitate better knowledge about city planning and design. The complex connections between cities and pandemics, however challenge traditional approaches to reviewing literature. In this article we adopted a rapid review methodology. We review the historical literature on respiratory pandemics and their documented connections to urban planning and design (both broadly defined as being concerned with cities as complex systems). Our systematic search across multidisciplinary databases returned a total of 1323 sources, with 92 articles included in the final review. Findings showed that the literature represents the multi-scalar nature of cities and pandemics – pandemics are global phenomena spread through an interconnected world, but require regional, city, local and individual responses. We characterise the literature under ten themes: scale (global to local); built environment; governance; modelling; non-pharmaceutical interventions; socioeconomic factors; system preparedness; system responses; underserved and vulnerable populations; and future-proofing urban planning and design. We conclude that the historical literature captures how city planning and design intersects with a public health response to respiratory pandemics. Our thematic framework provides parameters for future research and policy responses to the varied connections between cities and respiratory pandemics. Highlights: Comprehensive mapping of the literature linking urban planning, design and respiratory pandemics has yet to occur. We review the historical literature since 1900. We present and detail 10 themes developed across 92 articles. The presented framework provides parameters for future research and policy responses.